Comparison of Underground Coal Mining Methods Based on Life Cycle Assessment - Wu, Haoyuan; Yin, Zhiqiang; Zhang, Yuchen; Qi, Chao; Liu, Xian; Wang, Jianen (Frontiers in Earth Science, 2022)
Coal is China’s main source of energy, and its production causes a certain degree of air, water, and land resource pollution. Therefore, it is necessary to compare environmental pollution caused by different mining methods. When mining underground coal resources, different mining methods have different levels of environmental impacts. To identify the mining method with the least environmental impact, different mining methods were evaluated by means of a life cycle assessment using Simapro 9.0.0 software. The Ecoinvent v3 database was used to provide background data, and the results were calculated using the Eco-indicator99 method. The findings show that for a 20 m coal column, respiratory inorganics were identified as the dominant impact category based on normalized results, followed by fossil fuels, carcinogens, and climate change. The contribution analysis indicated that electricity and coal mining are fundamental in contributing to these significant impact categories and should be of particular concern. According to the sensitivity analysis, reducing mining activities and increasing extraction efficiency and use are the primary responses to addressing environmental pollution, followed by reducing environmental pollution caused by electricity and steel production. In addition, a summary comparison of the single scores of different mining methods suggests that the environmental burden of pillarless mining is the lowest, and as the width of the coal pillar gradually increases, its single score shows a trend of increasing and then decreasing. Therefore, the single score of non-pillar mining is the lowest compared to that of other mining methods and can be the optimal mining method. This study can provide a scientific basis for the selection of green mining and underground coal resource mining methods.